2009
DOI: 10.1093/annonc/mdn727
|View full text |Cite
|
Sign up to set email alerts
|

High coexpression of both insulin-like growth factor receptor-1 (IGFR-1) and epidermal growth factor receptor (EGFR) is associated with shorter disease-free survival in resected non-small-cell lung cancer patients

Abstract: A statistically significant association was observed between high coexpression of both IGFR-1 and EGFR and worse DFS in early NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 26 publications
6
83
2
Order By: Relevance
“…Cappuzzo et al (18) reported that a positive IGF-1R expression was significantly associated with squamous cell histology and grade III differentiation. Ludovini et al (19) reported that IGF-1R protein overexpression was associated with larger tumor size. Merrick et al (20) showed that higher IGF-1R scores were associated with adenocarcinoma and never-smokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cappuzzo et al (18) reported that a positive IGF-1R expression was significantly associated with squamous cell histology and grade III differentiation. Ludovini et al (19) reported that IGF-1R protein overexpression was associated with larger tumor size. Merrick et al (20) showed that higher IGF-1R scores were associated with adenocarcinoma and never-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Dziadziuszko et al (17) evaluated 189 NSCLCs and showed that the IGF-1R gene copy number is of prognostic value; nonetheless, IGF-1R protein expression upon immunohistochemical analysis was not related to survival. Ludovini et al (19) reported that IGF-1R protein expression alone was not significantly associated with survival, although high co-expression of both IGF-1R and epidermal growth factor receptor was associated with shorter Table IV. Subset analysis of overall survival in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The interplay of these two receptor pathways may lead to resistance by the tumor to inhibition of one receptor via compensatory upregulation/activation of the reciprocal receptor, and dual inhibition of EGFR and IGF-1R has been shown to improve anti-tumor activity and overcome resistance to therapy against a single receptor in preclinical models. [17][18][19][20][21][22][23][24] Moreover, co-expression of EGFR and IGF-1R has been reported in many human tumors, including lung, colorectal and pancreatic carcinoma, [25][26][27] supporting dual targeting of these two receptors in these indications. Clinically, EGFR inhibitors are known to be efficacious in only a subpopulation of cancer patients, and intense research for molecular predictors of clinical outcomes to EGFR targeted therapies has identified K-Ras mutation as a predictive biomarker of resistance to EGFR mAbs treatment in colorectal cancer and EGFR gene mutation or high copy number as strong indicators of response to EGFR TKIs in lung cancer.…”
Section: Generation Of Bispecific Antibody Directed Against Egfr and mentioning
confidence: 99%
“…17,18 Overexpression of EGFR and IGF-IR in NSCLC patients led to shorter disease-free survival. 19 It was also shown that dual silencing of IGF-IR and EGFR decreased proliferation and increased apoptosis in colon carcinoma cells. 20 Additionally, resistance to treatment with the EGFR inhibitor AG1478 increased IGF-IR levels, 21 and resistance to the EGFR inhibitor gefitinib was associated with a heterodimerization of EGFR with IGF-IR.…”
Section: Introductionmentioning
confidence: 99%